2020
DOI: 10.17263/jlls.759243
|View full text |Cite
|
Sign up to set email alerts
|

Bronfenbrenner's theory and teaching intervention: The case of student with intellectual disability

Abstract: The aim of this study is to highlight the importance of teaching interventions in accordance with Bronfenbrener's Ecosystem Theory. The research questions address, how reading skills are taught in the microsystem of school through a Targeted, Individual, Structured, Integrated Program for Students with Special Educational Needs (TISIPfSENs) and how meso-exo-, macro-and chrono-system shape the structure of the intervention to enhancing reading skills. The methodology refers to a case study of a student with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Inclusive education is based on a belief that the inclusion of children with special needs in mainstream schools is beneficial for their studies and growth (Nai-Kwai Lo, 2007). Bronfenbrenner's theory's central point relates to the interactions created between the developing and active individuals and the social context that surrounds them and influences them directly and indirectly (Panopoulos & Drossinou-Korea, 2020). The theory presents five ecological system theories that influence the psychological development of a learner.…”
Section: Linking Bronfenbrenner's (1990) Ecological Systems Theory In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusive education is based on a belief that the inclusion of children with special needs in mainstream schools is beneficial for their studies and growth (Nai-Kwai Lo, 2007). Bronfenbrenner's theory's central point relates to the interactions created between the developing and active individuals and the social context that surrounds them and influences them directly and indirectly (Panopoulos & Drossinou-Korea, 2020). The theory presents five ecological system theories that influence the psychological development of a learner.…”
Section: Linking Bronfenbrenner's (1990) Ecological Systems Theory In...mentioning
confidence: 99%
“…Inclusive education (IE) guidelines stipulate that such learners must be supported to thrive like typical developing learners. Bronfenbrenner’s ( 1990 ) ecological systems theory on human development suggests a learner’s ecology, which is made up of interwoven network systems to support learners with special needs such as DLD (Panopoulos & Drossinou-Korea, 2020 ). It has been suggested that inter-professional collaboration (IPC) amongst speech–language therapists (SLTs), educational psychologists, audiologists, social workers and teachers is likely to reflect the needs of a learner with DLD (Liu et al, 2018; as cited in McGregor, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical perspective assumed in this study is based on the Bronfenbrenner's ecological approach (16), which explains human development based on the interrelationship with different ecosystems, allowing us to understand the development of adaptive behavior (17,18). This model comprises: a) microsystem, integrated by the daily contexts of the person, such as the family, school, workplace; b) mesosystem, made up of the interactions between two or more microsystems where the human being grow up; c) exosystem, is the environment in which the person does not interact, but exerts an indirect in uence on it and; d) macrosystem, encompasses cultural beliefs, values, state policies, whose in uence affects other systems and the individual.…”
Section: Introductionmentioning
confidence: 99%
“…While the exosystem in uences through values and experiences, con guring a culture of inclusion or exclusion. On the other hand, the macrosystem, which comprises laws and regulations, is the regulatory framework, linked to the fundamental rights of people with intellectual disabilities that is usually violated (17).…”
Section: Introductionmentioning
confidence: 99%
“…Association between students resilience and exosystem is auxiliary interlinked among students, microsystem, and mesosystem (Crawford, et al, 2020;Fearnley, 2020). Macrosystem overarches traditions, values, ethnicity, lifestyle, and political system through developing overt and hidden ideologies (Bronfenbrenner, 1977;Panopoulos & Drossinou-Korea, 2020). Macrosystem indirectly affects parents, teachers, and peers active involvement.…”
Section: Introductionmentioning
confidence: 99%